Typology of Chinese Languages: An Introduction to the Special Issue - Umberto Ansaldo; Pui Yiu Szeto (Languages)
Of the world’s major language groups, the Sinitic (Chinese) branch of the Sino-Tibetan family stands out for the profound disconnect between its popular perception and its linguistic reality [...]